Free polyamine content during algal bloom succession in the East China Sea in spring 2010 - 刘艳 赵卫红 李彩艳 苗辉 (Chinese journal of oceanology and limnology, 2017)
We measured the concentrations and distribution of major polyamines（spermine, putrescine and spermidine） in seawater during successive spring algal blooms in an area of frequent harmful blooms in the East China Sea. Spermine, putrescine, and spermidine concentrations were analyzed by high performance liquid chromatography and ranged from 1–64, 7–81, and 0–19 nmol/L. Spermine was present at the highest concentrations, followed by putrescine and spermidine. In late April, when a diatom bloom dominated by Skeletonema costatum dispersed, polyamine concentrations increased, presumably as a result of diatom decomposition. In early May, when a dinoflagellate bloom dominated by Prorocentrum donghaiense occurred, the polyamine concentration decreased from the level seen in late April. The abundant polyamines that decomposed and were released during the diatom bloom in late April may have promoted the growth of P. donghaiense, resulting in its dominance.